A review of the Quaternary Scelidotheriinae (Mammalia, Xenarthra, Tardigrada) from the Tarija-Padcaya basin, Bolivia - Miño-Boilini, Ángel Ramón (2018)
The Mylodontidae Scelidotheriinae (Mammalia, Xenarthra, Tardigrada) are a diversified clade of South American fossil ground sloths, with a wide geographic distribution, especially in high and middle latitudes. According to the last revision, the Quaternary diversity includes the genera Scelidotherium, Catonyx, and Valgipes. The clade Scelidotheriinae is well represented in the Pleistocene of the Tarija-Padcaya basin, and the first mention of these ground sloths correspond to the middle of the XIX Century. Since then, several species (i.e., Scelidotherium tarijensis, Scelidodon tarijensis, Scelidotherium capellini) have been reported as inhabiting the Tarija-Padcaya basin during the Pleistocene. Despite the abundance of fossil records of Scelidotheriinae in this area, no modern taxonomic revisions are available. In consequence, in this contribution a revision of the remains assigned to Scelidotheriinae from the Tarija-Padcaya basin is accomplished, and some biostratigraphic and geographic implications are discussed. Our results show that one single species (Catonyx tarijensis) can be recognized in the studied area, whereas a supposed smaller one (Scelidotherium patrium) actually corresponds to juvenile specimens of C. tarijensis.